Comparative analysis of intestinal morphology and intestinal microbiota composition of bullfrogs (Aquarana catesbeiana) at different growth stages - Xie, Jingyi; Zheng, Xiaoting; Chen, Qiuyu; Liang, Xueying; Dong, Hongbiao; Zhou, Shengfu; Yuan, Xiaoquan; Zhang, Jiasong (Frontiers in Microbiology, 2026)
The intestinal microbiota is a complex and dynamic community that contributes to digestion and plays a crucial role in regulating immune health. In this study, post-metamorphic bullfrogs (Aquarana catesbeiana) at different ages (1, 2, 3, and 4 months) were investigated. Growth performance assessment, intestinal histomorphological analysis, and 16S rRNA sequencing were employed to systematically examine the dynamics and diversity of microbial communities in the small intestinal segments (duodenum, jejunum, and ileum). Results showed that bullfrog growth indices increased with age, with faster body weight gain during 2–3 months; notably, this was significantly positively correlated with intestinal morphological development (villus height and muscle layer thickness) (p < 0.05). In terms of microbial composition, Firmicutes, Proteobacteria, Bacteroidetes, Fusobacteria, and Actinobacteria were dominant phyla, while different intestinal segments harbored specific dominant genera. Among them, Cetobacterium was consistently detected throughout the growth period, suggesting it is likely the core symbiont in bullfrog intestines. Moreover, microbiota function varied with growth stages: at 1–2 months, Bifidobacterium and Cetobacterium synergistically participated in immune regulation and basic metabolism, whereas at 3–4 months, Weissella, Lactococcus, and Bacteroides became dominant, with their functions shifting toward efficient energy conversion. Additionally, Alpha diversity analysis showed a decreasing trend in the Simpson index with development, while Beta diversity analysis revealed that microbiota composition was similar among different intestinal segments at the same age but that significant differences existed in each segment during 2–3 months. Overall, this study reveals the specific distribution characteristics of probiotic microbiota in bullfrogs at different growth stages, thereby providing a scientific basis for screening growth-promoting frog-derived probiotics that match host physiological traits.